Cultural and chemical control of silvery-thread moss in creeping bentgrass putting greens - Raudenbush, Zane (Kansas State University, 2015)
Controlling and preventing the spread of silvery-thread moss (STM, Bryum argenteum Hedw.) in putting greens is a difficult task for superintendents. Once established, a STM infestation can quickly increase through the movement of asexual propagules, such as shoot fragments, bulbils and protonema. Many practices used by superintendents are likely aiding in the dispersal and establishment of propagules. Research is needed to help superintendents effectively control this very invasive pest. The objectives of this research were to: 1) Investigate the cumulative effect of cultivation on a STM infestation in a creeping bentgrass putting green, when used with or without light, frequent topdressing and the herbicide carfentrazone; 2) Determine if STM growth is reduced by spraying ammonium sulfate (AMS) compared to urea, and understand the effect of spray volume on STM growth; 3) Evaluate the effectiveness of a range of carfentrazone rates for postemergence STM control; and 4) Determine if altering the pH of irrigation water with sulfuric- or hydrochloric acid affects the growth of STM. Generally, cultivation and carfentrazone reduced STM cover; however, the greatest reduction in STM cover was achieved when cultivation treatments were used in conjunction with carfentrazone. Topdressing did not affect STM cover. Ammonium sulfate increased STM cover and dry weight compared to urea and an untreated control. Furthermore, spray volume did not affect STM cover at any rating date. Superintendents managing STM infestations should limit or avoid use of AMS as an N source. At 28 days after treatment (DAT) the ED[subscript]90 (dose required to cause 90% gametophyte injury) was 26.8 g ai ha[superscript]-1, and at 49 DAT ED[subscript]90 was 54.3 g ai ha[superscript]-1; both of these doses are substantially lower than the label rates for long- and short-term control, respectively. As compared with label recommendations, this research suggests lower carfentrazone rates, and longer intervals, may be effective for STM control in putting greens. Irrigation pH affected STM growth, with pH’s 5 and 6 having increased growth compared to pH’s 7 and 8. It was hypothesized a lower irrigation pH enabled STM to better withstand sodium stress.
Keywords: Carfentrazone; Bryum argenteum; Bryophytes; Agronomy (0285); Horticulture (0471)